A 2D copper-imidazolate framework without thermal treatment as an efficient ORR electrocatalyst for Zn–air batteries. Issue 46 (14th November 2022) - Franco, Ana; Salatti-Dorado, José Ángel; García-Caballero, Valentín; Lorca, Sebastián; Camacho, Luis; Cano, Manuel; Fernández-Romero, Antonio J.; Delgado, Juan J.; Giner-Casares, Juan J.; Carrillo-Carrión, Carolina
Abstract : A novel water-stable 2D Copper-Imidazolate Framework (2DCIF) exhibits outstanding electrocatalytic activity for the oxygen reduction reaction without the need for calcination. These 2DCIFs have been successfully used as air electrodes in Zn–air batteries. Abstract : To face unmet energy demands, the search for more stable, low-cost, and scalable electrocatalyst materials is imperative. Within this context, single-atom catalysts (SACs) have drawn considerable attention due to their maximum atom utilization. With this idea in mind, we have synthesized a new ultrathin and water-stable 2D Cu-based metal–organic framework (2DCIF), which presents a notable electrocatalytic activity for the oxygen reduction reaction (ORR) in alkaline media without the need for calcination, which makes the difference when compared to most MOF-based electrocatalysts. The designed MOF-based SAC consists of single-atom sites (isolated and accessible Cu) coordinated to imidazole carboxylic ligands, giving rise to Cu–N4 O actives sites confined in a 2D-nanostructured network. This unique structure, along with the ultrathin nanosheets that favor mass transport and electrical conductivity, and the high chemical stability of these 2DCIFs are the key features that endow them with excellent performance in the ORR, which occurs via a direct four-electron transfer pathway, with an onset potential of 0.86 V vs. RHE and a maximum current density of 6.4 mA cm −2 . These good catalytic properties of 2DCIFs have allowed their use as efficient air electrodes in alkaline flooded and all-solid-state Zn–air batteries. In the former case, 2DCIF-based air electrodes presented a specific power density of 91.2 kW cm −2 kg −1 and a specific capacity of 296.2 A h g −1, significantly exceeding the specific capacity values reported previously for other Cu-based catalysts. Besides, the specific capacity increased to 389.1 A h g −1 when 2DCIFs were tested in an all-solid-state Zn–air battery.